An investigation of a novel milk allergy-friendly food supplement program - Golding, Michael A.; Bhamra, Manvir; Harbottle, Zoe; Ben-Shoshan, Moshe; Gerdts, Jennifer D.; Roos, Leslie E.; Abrams, Elissa M.; Penner, Sara J.; St-Vincent, Jo-Anne; Protudjer, Jennifer L. P. (Frontiers in Allergy, 2024)
Introduction: Compared to households not managing food allergy, households managing food allergy are faced with greater direct and indirect costs. To address these cost burdens, we developed and piloted a milk allergy-friendly food supplement program for lower-and middle-income households managing a dairy allergy in a child age <6 years. Herein, we aimed to evaluate to the impact of this program on food costs, food security, and caregiver mental health using a longitudinal design.Methods: Participants living in or near the city of Winnipeg, in Manitoba, Canada were recruited from January to February 2022 via social media, word-of-mouth, and a database maintained by the principal investigator. Consenting participants took part in a 6-month allergen-friendly food supplement program that provided them with biweekly deliveries of allergen-friendly foods free of charge. To evaluate the impact of the program on food costs, food security, and well-being, participants completed a series of questionnaires at baseline, mid-point, and at the end of the program. Changes in these variables were assessed via a series of Friedman tests.Results: The final sample was comprised of 8 households. Relative to baseline, participants reported higher total direct food costs at midpoint (+5.6%) and endpoint (+13.5%), but these changes did not reach statistical significance. In contrast, total indirect food costs decreased over the course of the study relative to baseline (midpoint =-28.2%; endpoint =-18.5%), but the changes were not found to be statistically significant. Participants did, however, report a statistically significant decrease in costs related to lost time from work or school as a result of their child's food allergy at endpoint relative to baseline (-100%). Few changes in food security, caregiver wellbeing, or child food allergy quality of life were noted.Discussion: The provision of allergen-friendly foods helped keep grocery costs below the pace of inflation. Participants also reported reduced costs associated with missed time from work or school as a result of their child's food allergy. Despite these encouraging findings, a relatively high proportion of the current sample reported experiencing food insecurity throughout the study period, suggesting that additional financial support for families is needed.